Optimisation design of pine backrest chair based on Taguchi method. (2nd January 2017) - Ke, Q.; Zhang, F.; Zhang, Y.
Abstract : In this paper, the ANSYS finite element analysis is applied to the pine backrest chair models. During the structure design progress, the Taguchi method for the robust design is applied. By means of the signal-noise ratio (SNR) factor effect analysis, the optimal design scheme of the structural quality of pine backrest chair is determined that the backrest chair is designed as trapezoidal seat frame, upper waling, bottom waling with II type and leaning back rear leg. Based on the above condition, the maximum equivalent stress is improved by 9.05% than the initial one, the maximum deformation is ameliorated by 14.42% and the SNR is significantly improved. When robust design is on the basic of Taguchi method, the robustness of structure quality characteristics can be enhanced. At the same time, the overall strength and stiffness of the furniture structure can be improved and the design cost can be reduced.